1997
DOI: 10.4049/jimmunol.159.3.1444
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits IgE-mediated degranulation of mast cells and is the principal intermediate in IFN-gamma-induced suppression of exocytosis.

Abstract: IFN-gamma regulates various aspects of rodent peritoneal mast cell function, including mediator release, cell growth, TNF-alpha-mediated cytotoxicity, and MHC class II expression. We investigated whether the suppressive action of IFN-gamma on IgE/Ag-mediated degranulation of mast cells is mediated via synthesis of nitric oxide. Incubation of mouse peritoneal cells with L-NMMA, an inhibitor of nitric oxide synthase, or in medium lacking the nitric oxide precursor L-arginine reversed the inhibitory effect of IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, mast cell degranulation is regulated by intracellular calcium release from the endoplasmic reticulum and activation of protein kinase C (PKC), which depends on the activation of G-protein-coupled receptors (GPCRs) on the mast cell surface (Kimura et al, 1998;Nguyen et al, 2002;Kuehn and Gilfillan, 2007). Eastmond NC et al reported that NO directly inhibited the IgE-mediated secretory function of mast cells (Eastmond et al, 1997). OT promotes NO synthesis by cardiac myocytes and dorsal root ganglion (Jankowski et al, 2010;Gutkowska et al, 2014, Gong et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mast cell degranulation is regulated by intracellular calcium release from the endoplasmic reticulum and activation of protein kinase C (PKC), which depends on the activation of G-protein-coupled receptors (GPCRs) on the mast cell surface (Kimura et al, 1998;Nguyen et al, 2002;Kuehn and Gilfillan, 2007). Eastmond NC et al reported that NO directly inhibited the IgE-mediated secretory function of mast cells (Eastmond et al, 1997). OT promotes NO synthesis by cardiac myocytes and dorsal root ganglion (Jankowski et al, 2010;Gutkowska et al, 2014, Gong et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mast cell degranulation is regulated by intracellular calcium release from the endoplasmic reticulum and the activation of protein kinase C (PKC), which depends on the activation of G-protein-coupled receptors (GPCRs) on the mast cell surface (28-30). Eastmond NC et al reported that NO directly inhibited the IgEmediated secretory function of mast cells (31). OT promotes NO synthesis by cardiac myocytes (11,32) and dorsal root ganglion(DRG) neurons synthesize NO (33).…”
Section: Discussionmentioning
confidence: 99%
“…The number of mast cells routinely obtained is always greater in ovalbumin (OVA)-sensitized rats. The total cell yield from mice ranges from 1 to 3 × 10 6 mixed peritoneal cells, 3 to 6 × 10 5 of which will be mast cells (Coleman et al, 1993;Eastmond et al, 1997).…”
Section: Isolation and Culture Of Peritoneal Mast Cellsmentioning
confidence: 99%